Solve the system of equations using determinants
⎩ ⎪ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎪ ⎧ x − 2 y + z + 3 w = 7 x + y + 3 z + 2 w = 6 x + y − 2 z + w = 9 3 x + 4 y + 4 z + 2 w = 1 6 Give your answer as ( x + y + z + w ) 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
wow, I must appreciate your work, this is amazing ;)
Problem Loading...
Note Loading...
Set Loading...
Using the principle of minors to evaluate determinants, we have
D = ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ 1 1 1 3 − 2 1 1 4 1 3 − 2 4 3 2 1 2 ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ = 1 ∣ ∣ ∣ ∣ ∣ ∣ 1 1 4 3 − 2 4 2 1 2 1 1 4 3 − 2 4 ∣ ∣ ∣ ∣ ∣ ∣ − 1 ∣ ∣ ∣ ∣ ∣ ∣ − 2 1 4 1 − 2 4 3 1 2 − 2 1 4 1 − 2 4 ∣ ∣ ∣ ∣ ∣ ∣ + 1 ∣ ∣ ∣ ∣ ∣ ∣ − 2 1 4 1 3 4 3 2 2 − 2 1 4 1 3 4 ∣ ∣ ∣ ∣ ∣ ∣ − 3 ∣ ∣ ∣ ∣ ∣ ∣ − 2 1 1 1 3 − 2 3 2 1 − 2 1 1 1 3 − 2 ∣ ∣ ∣ ∣ ∣ ∣
D = 1 [ − 4 + 1 2 + 8 − ( − 1 6 + 4 + 6 ) ] − 1 [ 8 + 4 + 1 2 − ( − 2 4 − 8 + 2 ) ] + 1 [ − 1 2 + 8 + 1 2 − ( 3 6 − 1 6 + 2 ) ] − 3 [ − 6 + 2 − 6 − ( 9 + 8 + 1 ) ]
D = 2 2 − 5 4 − 1 4 + 8 4 = 3 8
N x = ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ 7 6 9 1 6 − 2 1 1 4 1 3 − 2 4 3 2 1 2 ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ = 7 ∣ ∣ ∣ ∣ ∣ ∣ 1 1 4 3 − 2 4 2 1 2 1 1 4 3 − 2 4 ∣ ∣ ∣ ∣ ∣ ∣ − 6 ∣ ∣ ∣ ∣ ∣ ∣ − 2 1 4 1 − 2 4 3 1 2 − 2 1 4 1 − 2 4 ∣ ∣ ∣ ∣ ∣ ∣ + 9 ∣ ∣ ∣ ∣ ∣ ∣ − 2 1 4 1 3 4 3 2 2 − 2 1 4 1 3 4 ∣ ∣ ∣ ∣ ∣ ∣ − 1 6 ∣ ∣ ∣ ∣ ∣ ∣ − 2 1 1 1 3 − 2 3 2 1 − 2 1 1 1 3 − 2 ∣ ∣ ∣ ∣ ∣ ∣
N x = 7 [ − 4 + 1 2 + 8 − ( − 1 6 + 4 + 6 ) ] − 6 [ 8 + 4 + 1 2 − ( − 2 4 − 8 + 2 ) ] + 9 [ − 1 2 + 8 + 1 2 − ( 3 6 − 1 6 + 2 ) ] − 1 6 [ − 6 + 2 − 6 − ( 9 + 8 + 1 ) ]
N x = 1 5 4 − 3 2 4 − 1 2 6 + 4 4 8 = 1 5 2
N y = ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ 1 1 1 3 7 6 9 1 6 1 3 − 2 4 3 2 1 2 ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ = 1 ∣ ∣ ∣ ∣ ∣ ∣ 6 9 1 6 3 − 2 4 2 1 2 6 9 1 6 3 − 2 4 ∣ ∣ ∣ ∣ ∣ ∣ − 1 ∣ ∣ ∣ ∣ ∣ ∣ 7 9 1 6 1 − 2 4 3 1 2 7 9 1 6 1 − 2 4 ∣ ∣ ∣ ∣ ∣ ∣ + 1 ∣ ∣ ∣ ∣ ∣ ∣ 7 6 1 6 1 3 4 3 2 2 7 6 1 6 1 3 4 ∣ ∣ ∣ ∣ ∣ ∣ − 3 ∣ ∣ ∣ ∣ ∣ ∣ 7 6 9 1 3 − 2 3 2 1 7 6 9 1 3 − 2 ∣ ∣ ∣ ∣ ∣ ∣
N y = 1 [ − 2 4 + 4 8 + 7 2 − ( − 6 4 + 2 4 + 5 4 ) ] − 1 [ − 2 8 + 1 6 + 1 0 8 − ( − 9 6 + 2 8 + 1 8 ) ] + 1 [ 4 2 + 3 2 + 7 2 − ( 1 4 4 + 5 6 + 1 2 ) ] − 3 [ 2 1 + 1 8 − 3 6 − ( 8 1 − 2 8 + 6 ) ]
N y = 8 2 − 1 4 6 − 6 6 + 1 6 8 = 3 8
N z = ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ 1 1 1 3 − 2 1 1 4 7 6 9 1 6 3 2 1 2 ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ = 1 ∣ ∣ ∣ ∣ ∣ ∣ 1 1 4 6 9 1 6 2 1 2 1 1 4 6 9 1 6 ∣ ∣ ∣ ∣ ∣ ∣ − 1 ∣ ∣ ∣ ∣ ∣ ∣ − 2 1 4 7 9 1 6 3 1 2 − 2 1 4 7 9 1 6 ∣ ∣ ∣ ∣ ∣ ∣ + 1 ∣ ∣ ∣ ∣ ∣ ∣ − 2 1 4 7 6 1 6 3 2 2 − 2 1 4 7 6 1 6 ∣ ∣ ∣ ∣ ∣ ∣ − 3 ∣ ∣ ∣ ∣ ∣ ∣ − 2 1 1 7 6 9 3 2 1 − 2 1 1 7 6 9 ∣ ∣ ∣ ∣ ∣ ∣
N z = 1 [ 1 8 + 2 4 + 3 2 − ( 7 2 + 1 6 + 1 2 ) ] − 1 [ − 3 6 + 2 8 + 4 8 − ( 1 0 8 − 3 2 + 1 4 ) ] + 1 [ − 2 4 + 5 6 + 4 8 − ( 7 2 − 6 4 + 1 4 ) ] − 3 [ − 1 2 + 1 4 + 2 7 − ( 1 8 − 3 6 + 7 ) ]
N z = − 2 6 + 5 0 + 5 8 − 1 2 0 = − 3 8
N w = ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ 1 1 1 3 − 2 1 1 4 1 3 − 2 4 7 6 9 1 6 ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ = 1 ∣ ∣ ∣ ∣ ∣ ∣ 1 1 4 3 − 2 4 6 9 1 6 1 1 4 3 − 2 4 ∣ ∣ ∣ ∣ ∣ ∣ − 1 ∣ ∣ ∣ ∣ ∣ ∣ − 2 1 4 1 − 2 4 7 9 1 6 − 2 1 4 1 − 2 4 ∣ ∣ ∣ ∣ ∣ ∣ + 1 ∣ ∣ ∣ ∣ ∣ ∣ − 2 1 4 1 3 4 7 9 1 6 − 2 1 4 1 3 4 ∣ ∣ ∣ ∣ ∣ ∣ − 3 ∣ ∣ ∣ ∣ ∣ ∣ − 2 1 1 1 3 − 2 7 6 9 − 2 1 1 1 3 − 2 ∣ ∣ ∣ ∣ ∣ ∣
N w = 1 [ − 3 2 + 1 0 8 + 2 4 − ( − 4 8 + 3 6 + 4 8 ) ] − 1 ( 6 4 + 3 6 + 2 8 − ( − 5 6 − 7 2 + 1 6 ) ] + 1 [ − 9 6 + 2 4 + 2 8 − ( 8 4 − 4 8 + 1 6 ) ] − 3 [ − 5 4 + 6 − 1 4 − ( 2 1 + 2 4 + 9 ) ]
N w = 6 4 − 2 4 0 − 9 6 + 3 4 8 = 7 6
x = D N x = 3 8 1 5 2 = 4
y = D N y = 3 8 3 8 = 1
z = D N z = 3 8 − 3 8 = − 1
w = D N w = 3 8 7 6 = 2
The desired answer is ( 4 + 1 − 1 + 2 5 ) 2 = 3 6
Notes:
D = determinant of the coefficients of the variables
N x = determinants taken from D replacing the coefficients of x by their corresponding constant terms leaving all other terms unchanged
N y = determinants taken from D replacing the coefficients of y by their corresponding constant terms leaving all other terms unchanged
N z = determinants taken from D replacing the coefficients of z by their corresponding constant terms leaving all other terms unchanged
N w = determinants taken from D replacing the coefficients of w by their corresponding constant terms leaving all other terms unchanged